New subclass of harmonic univalent functions defined by a generalised differential operator (Subkelas baharu fungsi univalen harmonik yang ditakrif oleh pengoperasi pembeza teritlak) - Salma Faraj Ramadan,; Maslina Darus, (Penerbit Universiti Kebangsaan Malaysia, 2012)
Let SH denote the class of functions =fhg+ which are harmonic univalent and sense preserving in the unit disk U. Earlier we have introduced a class of harmonic functions defined by a generalised differential operator. In this paper we introduce a new subclass of this class and obtain results on coefficient bounds, distortion and extreme points.